Effect of relaxation-dependent adhesion on pre-sliding response of cartilage. Issue 5 (23rd May 2018) - Han, Guebum; Eriten, Melih
Abstract : Possible links between adhesive properties and the pre-sliding (static) friction response of cartilage are not fully understood in the literature. The aims of this study are to investigate the relation between adhesion and relaxation time in articular cartilage, and the effect of relaxation-dependent adhesion on the pre-sliding response of cartilage. Adhesion tests were performed to evaluate the work of adhesion of cartilage at different relaxation times. Friction tests were conducted to identify the pre-sliding friction response of cartilage at relaxation times corresponding to adhesion tests. The pre-sliding friction response of cartilage was systematically linked to the work of adhesion and contact conditions by a slip-based failure model. It was found that the work of adhesion increases with relaxation time. Also, the work of adhesion is linearly correlated to the resistance to slip-based failure. In addition, as the work of adhesion increases, the adhered (stick) area at the moment of failure increases, and the propagation rate of the annular slip (crack) area towards its centre increases. These findings offer a mechanistic explanation of the pre-sliding friction behaviour and stick–slip response of soft hydrated interfaces such as articular cartilage and hydrogels. In addition, the linear correlation between adhesion and threshold to slip-based failure enables estimation of the adhesive strength of such interfaces directly from the pre-sliding friction response (e.g. shear wave elastography).